Green synthesis of NiO nanoparticle using Punica granatum peel extract and its characterization for methyl orange degradation. (March 2023) - Mandal, Biplab Kumar; Mandal, Rahul; Sikdar, Suranjan; Sarma, Sidananda; Srinivasan, Ananthakrishnan; Chowdhury, Subhajit Roy; Das, Bhaskar; Das, Rahul
Abstract: A simple environment friendly green synthesis method was employed to fabricate nickel oxide nanoparticles (NiO-NPs). Punica granatum peel extract was used in the place of traditional hazardous chemicals which generally act as stabilizing, reducing and capping agents. High resolution transmission electron microscopy images revealed that the size of the NPs ranged from 13.0 nm to 42.0 nm. The single-phase face-centered cubic crystal structure of the NiO-NPs with Fm3̅m space group was confirmed by X-ray diffraction studies. Direct and indirect optical band gap energies were found to be 3.34 eV and 2.72 eV, respectively, from optical absorption curves. The experimental optical bandgap results are close to the theoretically determined direct and indirect band gap values of 3.63 eV and 2.54 eV, respectively. Magnetometry studies revealed ferromagnetism at room temperature characterized by a saturation magnetization of 0.297Am 2 /kg and coercivity of 75.6 × 10 -4 T along with an antiferromagnetic contribution which was estimated from the susceptibility data to be 9.4 × 10 -2 Am 2 /kg.T. The prepared NiO-NPs were used as catalyst along with NaBH4 to clean water containing toxic organic pollutant methyl orange. Graphical Abstract: ga1